Determinants of Dollarization : The Banking Side - Terrones, Marco (IMF Working Papers; Working Paper, 2000)
Dollarization in financial intermediation has exhibited a widely diverse pattern across countries. Empirical work relating it to macroeconomic variables has had only limited success in explaining the phenomenon. This paper presents a two-currency banking model to show that deposit and loan dollarization are determined by a broader set of factors. These include interest rates and exchange rate risk, as well as structural factors related to costly banking, credit market imperfections, and availability of tradable collateral. The direction in which dollarization tends to move with macroeconomic shocks is shown to depend on those factors as well as on initial dollarization levels.